P177 Left atrial strain in patients with cardiac amyloidosis. Relationship to left atrial amyloid deposition focusing on prognosis. (13th January 2020) - Misumi, K; Miura, H; Morita, Y; Amano, H; Ueda, H I; Izumi, C; Fukuda, T; Noguchi, T; Yasuda, S
Abstract: Background:  In cardiac amyloidosis (CA), the left atrium (LA) is frequently infiltrated by the amyloid fibrils. It is currently known that LA strain is a marker of LA function and prognosis in many cardiac diseases, however its significance in CA remains unknown.  Purpose:  Our aim was to investigate correlation between LA strain measured by Cardiovascular Magnetic Resonance (CMR) and amyloid deposit in LA, and also evaluate the LA strain on the prognostic significance.  Methods and results:  Of 74 consecutive patients with biopsy-proven CA, we analyzed 42 patients (age 72 ± 10 years; 76 % males) with contrast-enhanced CMR, and examined LA late gadolinium enhancement (LGE) and CMR derived LA strain using feature tracking method. Of the 42 patients, 29 patients (69 %) was transthyretin cardiac amyloidosis (ATTR-CA) in the majority. We divided these 42 patients into two groups according to the CMR measured peak atrial longitudinal strain (PALS) (> = or < median); high-strain (> = 6.67 %, n = 21) and low-strain (＜ 6.67 %, n = 21) and compared the patient's characteristics, blood test data, echocardiography and CMR parameters. There were no significant differences between two groups in these parameters but in the extent of LA-LGE (54 % vs 80 %, p = 0.008). The PALS correlated with the extent of LA-LGE (ρ= 0.50, p = 0.001). In multivariate analysis including LVEF, E/e' and BNP, LA-LGE was an independent determinant of PALS. During three-year follow up, the LA strain significantly related to heart failure hospitalization in the ATTR-CA patients (p = 0.036)(Figure).  Conclusions:  In CA patients, CMR measured LA longitudinal strain correlates with the LA-LGE. It also provides useful information for poor prognosis of patients with ATTR-CA.